Integrated reservoir studies - Cosentino, Luca (Editions Technip, 2001)
Annotation The goal of this book is to highlight the difference between an integrated reservoir study and a traditional one. The benefits of integrated studies are outlined, and consider its implications for everyday working conditions. Technical and professional challenges are discussed and necessary changes are detailed, with emphasis on the role of the project leader. Chapters consider elements like the integrated database, the integrated geological model, rock properties, hydrocarbon in place determination, reservoir engineering, numerical reservoir simulation, and planning for a study. Cosentino is a reservoir engineer and project manager for a private firm. c. Book News Inc.
Keywords: Petroleum -- Geology.; Hydrocarbon reservoirs.; elektronické knihy; electronic books